Positive Ground State Solutions for a Schrödinger-Newton System with Negative Critical Nonlocal Term (Journal of Partial Differential Equations, 2025)
We consider the following Schrödinger-Newton system with negative critical nonlocal termwhere $a$ and $f$ satisfy some certain conditions. By using the variational method andanalytical techniques, we obtain the existence of positive ground state solutions whichimproves the recent results in the literature.